Airway stenting for patients with airway stenosis because of small cell lung cancer. (7th May 2018) - Oki, Masahide; Saka, Hideo
Abstract: Background: Airway stenting has been reported to be useful for patients with malignant airway stenosis as a bridge to tumour‐specific therapy, such as chemotherapy and radiation therapy, as well as palliative therapy. However, its role in patients with small‐cell lung cancer (SCLC), the most aggressive lung cancer subtype, is unclear. We investigated the efficacy of airway stenting for patients with airway stenosis resulting from SCLC. Methods: All stenting procedures were performed using both rigid and flexible bronchoscopes under general anaesthesia. Among 512 patients who underwent rigid bronchoscopy during a 9‐year period at a single centre, those who underwent airway stenting for airway stenosis because of SCLC were retrospectively reviewed. Results: Twenty‐one SCLC patients with airway stenosis who underwent stenting were eligible for analysis. Twelve patients (57%) were chemoradiotherapy‐naïve. Supplemental oxygen was reduced after the procedure in 11 out of 12 patients (92%) who had previously required it. Fourteen patients (67%) received tumour‐specific therapy after the procedure. The median post‐procedural survival was 47 days (range, 5‐617 days). Longer survival was associated with the performance of post‐procedural tumour‐specific therapy, low serum lactate dehydrogenase levels and either tracheal or bronchial stenosis. Conclusions: SCLC patients with airway stenting experienced longer survival when post‐procedural tumour‐specific therapy was performed, when they showed low serum lactate dehydrogenase levels, and when they had either tracheal or bronchial stenosis.